Use of an anti-cancer compound - Abdul, Ahmad Bustamam; Hakim Abdullah, Muhd Nazrul; Lajis, Mohd Nordin; Tailan, Nirmala Devi; Mohd Zain, Zetty Nadia (2012)
The present invention relates to a compound represented by the formula (I), method of preparation, pharmaceutical preparation containing said compound, and the use of said compound in the manufacture of a pharmaceutical preparation for the prevention and treatment of cancer by way of inhibiting the proliferation of carcinoma cells of the cervix and ovaries.